Kinetic Energy Recovery System - Manikandan, J.; Praveen Kumar, M. (International Journal of Psychosocial Rehabilitation, 2019)
Kinetic energy recovery system is a method of conserving energy lost in machines. I chose this paper to show how this system can be used in the bicycles. The basics of KRES technology is that it stores the kinetic energy of a moving vehicle when braking and then releases it back into the car’s drive train during acceleration. The system consists of a flywheel by a transmission to the driver train. The main parts of the system are driver unit, transmission, energy storing unit, energy retrieval unit.